Ganoderic acid loaded nano-lipidic carriers improvise treatment of hepatocellular carcinoma. (1st January 2019) - Rahman, Mahfoozur; Al-Ghamdi, Shareefa Abdullah; Alharbi, Khalid S; Beg, Sarwar; Sharma, Kalicharan; Anwar, Firoz; Al-Abbasi, Fahad A; Kumar, Vikas
Abstract: This work evaluates nano-lipid carrier of ganoderic acid (GA) and molecular docking on various cancer signaling pathways, an attempt to improve the hepatic condition associated with hepatic carcinoma (HCC) induced by diethyl-nitrosamine (DEN) in Wistar rats. Molecular docking mechanism of GA was performed through binding simulation analysis for various cancer signaling pathway, viz., Bcl-2, Pl3K, NF-κB, Akt/PKB, and Stat-3. Double emulsion solvent displacement method was implied for preparation of GA-loaded nano-lipid carrier. GA-NLCs were evaluated for drug loading capacity, entrapment efficiency, particle size, gastric stability, in vitro drug release, cytotoxicity, cellular uptake, and in vivo studies including macroscopical, hepatic injury markers, non-hepatic, biochemical, antioxidant parameters, and histopathological evaluation. HCC was induced by intraperitoneal injection of DEN (200 mg/kg). Both in vivo and molecular docking results were compatible in establishing the alteration in hepatic nodules, hepatic, non-hepatic, and antioxidant parameters, in a significant manner ( p  < .001) by GA and GA-NLC along with signal alteration of Bcl-2, Pl3K, NF-κB Akt/PKB, and Stat-3 pathway. Histopathological observation confirmed and supported the above result by GA and GA-NLC. On the basis of our results, we can advocate that, GA interferes with various cancer signaling proteins involved in pathogenesis of cancer and was able to cease the progression of disease. Additionally, GA-NLCs proved its chemoprotective effect against the DEN-induced HCC by modulation of hepatic and non-hepatic parameters through various mechanisms.